ANALYSIS OF THE CHEMICAL CHARACTERISTICS OF POWDERED BROTH MADE FROM MULTISPECIES MACROALGAE COLLECTED FROM THE WATERS OF ANYER, BANTEN PROVINCE - Jehan Fadhila; Rifki Prayoga Aditia; Devi Faustine Elvina Nuryadin (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Seaweed has significant potential to be developed as a raw material for natural powdered broth due to its high nutritional value and abundance of bioactive compounds. This study aimed to analyze the chemical characteristics and consumer acceptability of powdered broth produced from various seaweed species collected from the waters of Anyer. The study employed a completely randomized design (CRD) consisting of four treatments with three replications. The treatments included Gracilaria sp., Ulva lactuca, Kappaphycus alvarezii, and Sargassum sp. The analyzed parameters included NaCl content, moisture content, protein content, fat content, ash content, and hedonic evaluation of appearance, aroma, taste, and texture. Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT), while hedonic data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test. The results showed that differences in seaweed species had a significant effect (p < 0.05) on all evaluated parameters. Based on the effectiveness index analysis using the De Garmo method, powdered broth produced from Ulva lactuca was identified as the best treatment. The product exhibited chemical characteristics consisting of 0.0023% NaCl content, 4.420% moisture content, 16.74% protein content (dw), 1.64% fat content (dw), and 14.3% ash content (dw). The hedonic test scores were 7.50 for appearance (like), 6.67 for aroma (slightly like), 5.97 for taste (neutral), and 6.90 for texture (slightly like).